Pengaruh rasio keuangan terhadap prediksi perubahan laba bersih perusahaan manufaktur di industri makanan dan minuman - Oktaviansah, Mohamad Rizqi; Asiyah, Binti Nur (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this research is to see how the current ratio (CR), total assets turnover (TATO), debt to assets ratio (DAR), and gross profit margin (GPM) affect the earnings of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. Panel data regression with Eviews12 was utilized for data analysis. Based on specified criteria, 67 organizations were chosen as the research sample from a pool of 140. According to the findings of this study, the Current Ratio (CR) and the Debt to Asset Ratio (DAR) have no substantial positive effect on earnings. TATO and GPM boost profits. As a result, the financial ratios analyzed concurrently have a considerable effect on profit changes.